Neonatal bowel strangulation: Rare presentation of congenital diaphragmatic hernia. Issue 11 (November 2016) - Arena, Salvatore; Scalfari, Gianfranco; Turiaco, Nunzio; Marseglia, Lucia; Perrone, Patrizia; Gitto, Eloisa; Romeo, Carmelo
Abstract: We report a case of congenital diaphragmatic hernia (CDH) with perinatal bowel strangulation requiring intestinal resection. Ten hours after birth, the newborn started to be lethargic and developed bilious emesis. X‐ray documented distended loops of bowel with air fluid levels in the abdomen and a gasless, non‐homogeneous opacity of the left hemithorax, a right mediastinal shift and loss of the sharp left hemidiaphram line. On gastrographin enema the left colon was above the adjacent left diaphragm. Emergency surgery was performed at 16 h of age. The entire small bowel appeared reddish and compromised. After 24 h, second‐look laparotomy was performed and only 25 cm of small bowel were viable. The postoperative period was uneventful. Neonatal bowel strangulation in CDH should be taken into account when estimating postnatal morbidity and mortality and, even if CDH treatment is not an emergency procedure, if gastrointestinal symptoms prevail over respiratory symptoms, surgery should be carried out without delay.